The directorial leadership of the rector and its influence on the teaching commitment of educational institutions of Aguazul - Casanare - Arenas Parada, Alba Luz (Rastros Rostros, 2022)
The general objective of this research is to determine the influence of the director's leadership on the teaching commitment of the educational institutions of Aguazul - Casanare; where the type of research is basic or pure, the design is non-experimental, at an explanatory level with a quantitative approach, the information was collected by cross section, the sample is 134 teachers considering three institutions (Camilo Torres Restrepo with 49, San Agustín with 43 and Jorge Eliecer Gaitán with 42) chosen at random. The technique used is the survey and it is applied through a questionnaire as an instrument.The levels of leadership considered adequate to characterize the rector of each institution were analyzed, highlighting the prioritization of goal achievement and commitment to the entity through the measurement of affective commitment. Therefore, the influence of the managerial leadership factor is presented.
Keywords: achievement of objectives; strategic objectives; commitment of the entity; executive leadership